1999
DOI: 10.1590/s0074-02761999000200014
|View full text |Cite
|
Sign up to set email alerts
|

The Seroprevalence of Equine Trypanosomosis in the Pantanal

Abstract: Since little information is available on the epizootiological status of Trypanosoma evansi in SouthAmerica and particularly Brazil, we evaluated equine serum samples collected in 1993, 1994, 1995 and 1997

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Regarding Trypanosoma spp., the ELISA technique had an antibody prevalence of 50.4%, which was lower than the prevalence observed by Dávila et al (15) in a study in Pantanal, Mato Grosso do Sul, in which a prevalence of 79.2% was observed. When analyzed by RIFI, the samples had a prevalence of 18.84%, which was also lower than the prevalence found by Herrera et al (16) , who observed "Baixadeiros" horses: prevalence of anti-Trypanosoma spp.…”
Section: Discussioncontrasting
confidence: 67%
“…Regarding Trypanosoma spp., the ELISA technique had an antibody prevalence of 50.4%, which was lower than the prevalence observed by Dávila et al (15) in a study in Pantanal, Mato Grosso do Sul, in which a prevalence of 79.2% was observed. When analyzed by RIFI, the samples had a prevalence of 18.84%, which was also lower than the prevalence found by Herrera et al (16) , who observed "Baixadeiros" horses: prevalence of anti-Trypanosoma spp.…”
Section: Discussioncontrasting
confidence: 67%
“…Also, the higher number of tabanid species near the beginning and the end of the rainy period was similar to that reported for the Oriental Amazon (Gorayeb 1993). The high abundance of most tabanid species during the rainy season, particularly those potentially important as mechanical vectors (such as T. importunus), may explain the outbreaks of equine trypanosomosis (Trypanosoma evansi) as well as the temporal variation of T. evansi seroprevalence in equines previously reported in the Pantanal (Silva et al 1995, Dávila et al 1999. A seasonal sucession of the most abundant species was observed and may be associated with a strategy to reduce interspecific competition (Rafael 1982).…”
Section: Discussionmentioning
confidence: 82%
“…Sporadic outbreaks in horses occur in the different sub‐regions, but some areas are believed to be T. evansi‐free . 76,77 According to Seidl et al , 78 the estimated total cost of T. evansi to the Pantanal region cattle ranchers is about US$2.4 million and 6,462 per year.…”
Section: Current Statusmentioning
confidence: 99%